Напрямки застосування кореляційно-регресійного аналізу та коефіцієнтного методу фінансового аналізу для оцінки інвестиційної привабливості підприємства - Стригуль, Лариса Станіславівна (Тернопільський інститут агропромислового виробництва НААН України, 2012)
У статті розглянуто наукові основи визначення інвестиційної привабливості підприємства за допомогою кореляційно-регресійного та коефіцієнтного методів фінансового аналізу. Проведено аналіз показників фінансової звітності підприємств машинобудівної галузі. Розроблено пропозиції щодо вдосконалення системи оцінки рівня інвестиційної привабливості підприємства.

The article reviews the scientific basis of determination of investment appeal of the enterprise with the help correlation-regression and coefficient methods of the financial analysis are considered. Analysis of the present level of indicators of the financial reporting of the enterprises of machine-building industry is carried out. Suggestions concerning improvement of system of an estimation of level of investment appeal of the enterprise are developed.
Directions of application korreljatsionno-regressionnogo of analysis and coefficient method of the financial analysis for the estimation of investment appeal of the enterprise
Keywords: показники фінансові; звітність фінансова; галузь машинобудівна; система оцінювання; investment appeal; coefficient method; financial indicators; financial reporting; enterprise